A genre analysis of laptop and computer press releases / Christina Devi Kulandasamy - Christina Devi , Kulandasamy (2019)
Press Release (PR) is an important medium in carrying information about new products, services and policies. This study investigates the communicative purposes of PRs and its evolution from merely informational to include promotional element as well. Online laptop and computer PRs from Lenovo, Dell and HP are analysed to determine the move structure. For this purpose, the framework of Catenaccio (2008) is adopted as it is closely related to online product PRs. To further the investigation, the linguistic structures of the PR are also examined. Linguistic features like adjectives, nominal and binominal expressions are used to realise the communicative purposes in the PRs. Both quantitative and qualitative methods are employed in carrying out this research. The study shows that more than one communicative purpose is present in online product PRs; information, promotion and persuasion. However, they are subjected to some limitations as focus is given to the written structure and not the images or videos that are added in the website.